Improvements in functional exercise performance at 6 months following bariatric surgery: A prospective cohort study - Gorek Dilektasli, Asli; Coşkun, Funda; Karadag, Mehmet; Dilektasli, Evren (The European Research Journal, 2025)
Objectives: Successful weight loss after bariatric surgery has been associated with a variety of improvements in health status. Delayed heart rate recovery after the six-minute walking test (6MWT) is associated with morbidity and mortality in various cardiac and respiratory diseases. We aimed to evaluate the effect of bariatric surgery on functional exercise performance and autonomic dysfunction in patients who had undergone laparoscopic sleeve gastrectomy. Methods: Pre-operative and post-operative (6 months) demographics, comorbidities, weight, and height of the patients undergoing laparoscopic sleeve gastrectomy were recorded. All patients underwent a 6MWT. 6MWT was performed according to the American Thoracic Society standards. Additionally, heart rate (HR) and oxygen saturation were assessed at rest, at the end of the test, and in the first minute following testing. Autonomic dysfunction was assessed by heart rate recovery (HRR), which was calculated as the difference between the maximum HR reached during the 6MWT and the HR at the first minute after the test. Patients were classified depending on whether their HRR was slow (HRR<12 beats, “delayed recovery”) or more rapid (HRR≥12 beats, “non-delayed recovery”). Results: A total of 62 patients were prospectively enrolled. The mean age of the patients was 36.8±9.1 years and 74% were female. Pre-operative and post-operative body mass indices were 48.5±5.2 kg/m2 and 34.4±3.5 kg/m2, respectively (P<0.001). Excess weight loss was 52.7±12.7%. Post-operative six-minute walking distance significantly improved compared to pre-operative period (406±48 meters vs. 443±52 meters, P<0.001). Compared with pre-operative period, perceived breathlessness and fatigue at the end of the 6MWT decreased from 1.3±1.5 to 0.4±0.9 Borg units (P<0.001), and 3.2±2.1 to 0.8±1.4 Borg units (P<0.001), respectively. We observed a remarkable, but statistically non-significant increase in the number of patients in the delayed HRR group from 21% (n=13) to 42% (n=26) in the postoperative period, compared to the preoperative assessment (P=0.12). Conclusions: Laparoscopic sleeve gastrectomy is associated with rapid weight loss and improvements in perceived exertional dyspnea, fatigue and six-minute walking distance at 6 months after surgery. Failure of the heart rate to fall after cessation of exertion, a delayed HRR, has previously been found to be associated with increased mortality in cardiac failure. Further investigation is required to examine the physiological mechanisms involved in autonomic dysfunction, and consequences of delayed HRR after rapid weight loss by bariatric surgery.